2004
DOI: 10.1021/ma049370o
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics in Poly(ethene-alt-N-alkylmaleimide)s As Studied by Broadband Dielectric Spectroscopy

Abstract: Broadband dielectric spectroscopy has been used to analyze the molecular dynamics in a set of nine poly(ethene-alt-N-alkylmaleimide)s. The polymers were studied in the frequency range from 0.1 Hz to 10 MHz and at temperatures between 120 and 500 K. The alternating maleimide copolymers possess alkyl side chains varying in length from methyl to octadecyl. Four relaxation processes are observed:  (i) a (secondary) β-relaxation corresponding to librational fluctuations of the terminal end group of the alkyl side c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(47 reference statements)
0
7
1
Order By: Relevance
“…This value corresponds to 8.7 kJ per repeating unit of the polymer main chain. Kremer and coworkers [16] reported that the DH c value for poly(1d-altethylene) was 45.9 J Á g À1 (i.e., 17.3 kJ per repeating unit), being higher than the DH c value for poly(1d-alt-IB) in the present study. This is because the methyl groups of the IB repeating units in the main chain prevent reorganization of the methylene units in the side chains.…”
Section: Effect Of Side-chain Crystallizationcontrasting
confidence: 69%
“…This value corresponds to 8.7 kJ per repeating unit of the polymer main chain. Kremer and coworkers [16] reported that the DH c value for poly(1d-altethylene) was 45.9 J Á g À1 (i.e., 17.3 kJ per repeating unit), being higher than the DH c value for poly(1d-alt-IB) in the present study. This is because the methyl groups of the IB repeating units in the main chain prevent reorganization of the methylene units in the side chains.…”
Section: Effect Of Side-chain Crystallizationcontrasting
confidence: 69%
“…Primary aliphatic amines were used because of their fast reaction in solution with anhydride groups at low temperatures, without the need of a catalyst. The reaction with amines has been used extensively for MA copolymers, such as poly(styrene-co-MA), 47,48 poly(ethylene-co-MA), 48,49 and poly(propylene-co-MA), 47 usually to obtain maleimide copolymers. It is well known that the reaction of anhydride unit of MA copolymers with alkylamine proceeds via formation of an amide-acid linkage which then undergoes ring closure to form an imide structure.…”
Section: Nanostructurementioning
confidence: 99%
“…The Arrhenius-type temperature dependence relaxation rate with low activation energy (w20 AE 5 kJ/mol, see Table 4) and the weak dielectric strength (D3 < 0.05) are characteristic of localized fluctuations [36]. This process is assigned to librational fluctuations of the alkoxy linker [37,38]. Since the aliphatic spacer itself is nonpolar, its mobility can be dielectrically active only if some adjacent polar group is connected to it, for example an oxygen atom.…”
Section: The G B -Processmentioning
confidence: 99%